Influence of indigenous non-Saccharomyces yeast strains on the physicochemical and sensory properties of wine fermentation: a promising approach to enhancing wine quality - Thivijan, Sathivel; Pavalakumar, Dayani; Gunathunga, Chathuri J.; Undugoda, Lanka J. S.; Manage, Pathmalal M.; Nugara, Ruwani N.; Bandara, Pasan C.; Thambugala, Kasun M.; Al-Asmari, Fahad; Promputtha, Itthayakorn (Frontiers in Cellular and Infection Microbiology, 2024)
This study explores the potential of indigenous non-Saccharomyces yeasts isolated from Vitis vinifera L. grape skins to improve the quality of regional wines by enhancing their physicochemical and sensory characteristics. Five promising yeast strains were identified at different stages of fermentation: Hanseniaspora opuntiae (J1Y-T1), H. guilliermondii (Y5P-T5), H. uvarum (JF3-T1N), Pichia kudriavzevii (Y8P-T8), and Starmerella bacillaris (WMP4-T4). Among these, H. uvarum and S. bacillaris were particularly noteworthy due to their superior alcohol production, achieving levels of 8.16 ± 0.05% and 8.04 ± 0.04% (v/v), respectively, and demonstrating higher alcohol tolerance even in later fermentation stages. Hanseniaspora uvarum also showed exceptional resilience, with a half-life of 3.34 ± 0.03 days and a Km value of 1.0200 ± 0.0100 mol L⁻¹, achieving the highest biomass even in the later stages of fermentation. High-Performance Liquid Chromatography analysis revealed that while tartaric acid levels remained constant, malic acid content decreased, and acetic acid was produced by all strains. Solid-Phase Microextraction-Gas Chromatography Mass Spectrometry identified ethyl acetate as the dominant volatile compound, with H. uvarum producing the highest concentration (43.411 ± 1.602%), contributing to a fruitier aroma and flavor. The combined attributes of H. uvarum higher alcohol content, enhanced fruity notes, improved clarity, lower acetic acid (0.52 ± 0.03 g L⁻¹), and significant residual sugar (162.37 ± 2.48 g L⁻¹) make it a promising candidate for improving the overall quality of regional wines. Incorporating H. uvarum into mixed starter cultures with specific Saccharomyces strains could further optimize the wine fermentation process.